2017
DOI: 10.5897/jphe2016.0891
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of precancerous cervical lesion and associated factors among women in North Ethiopia

Abstract: Literature shows that cervical cancer is very prevalent among women living in low resource settings.Once it progresses to invasive cervical cancer, its cost is very high. Thus, screening cervical cancer is highly recommended in poor settings including Ethiopia, where the disease burden is very high. However, little is documented on the prevalence and determinants of precancerous cervical lesion among healthy women. Thus, this study aimed to assess the prevalence and factors associated with precancerous cervica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The current study found that women who encountered lifetime STIs have a higher risk of acquisition of PCL. The possible reason for the association might be due to the fact that HPV is the main cause for both PCL and STI [ 3 , 33 ]. This is consistent with previous findings in Ethiopia [ 2 , 17 , 34 ] and Uganda [ 14 ] which deduced that STI is a risk factor for a premalignant cervical lesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study found that women who encountered lifetime STIs have a higher risk of acquisition of PCL. The possible reason for the association might be due to the fact that HPV is the main cause for both PCL and STI [ 3 , 33 ]. This is consistent with previous findings in Ethiopia [ 2 , 17 , 34 ] and Uganda [ 14 ] which deduced that STI is a risk factor for a premalignant cervical lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The odds of being positive for PCL were three times higher among women having multiple sexual partners than monogamous women. This association is possibly due to the sexually transmitted nature of HPV, perhaps reflecting a greater likelihood of multiple HPV exposures and thus stochastically to greater opportunity for HPV persistence and progression to PCL [ 3 , 35 ]. This is similar with the findings of previous studies conducted in Ethiopia [ 2 , 17 , 18 ] and Uganda [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a study conducted in Aksum, Ethiopia there was a strong association between STI and the development of cervical cancer [AOR = 49.88 (95% CI 16.59, 149.91)] [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Our finding was also higher than the study conducted in the North part of Ethiopia which showed 6.7% precancerous cervical lesion. 12 This could be due to study area and study period difference.…”
Section: Discussionmentioning
confidence: 99%